Assessment of Serum Levels of Total Bile Acids in Chronic Kidney Disease Patients on Hemodialysis with and without Uremic Pruritus - Mustafa Sh. Abdulqahar; Ali A. Kasim (Iraqi Journal of Pharmaceutical Sciences, 2025)
Chronic kidney disease patients undergoing hemodialysis are frequently suffering from uremic pruritus, which can be quite uncomfortable. Uremic pruritus affects over 40% of hemodialysis patients. Bile acids have been implicated in the pathogenesis of pruritus; especially in conditions associated with cholestasis. The purpose of the study is to investigate the serum levels of total bile acids in chronic kidney disease patients on hemodialysis, with and without uremic pruritus. Ninety adults, chronic kidney disease patients who were on chronic hemodialysis at the hemodialysis unit at Al-Fallujah Teaching Hospital in Fallujah City, Iraq, were involved. Patients were grouped equally in two groups; according to the presence or absence of pruritus, based on the itching severity scale. Serum levels of total bile acids, urea, creatinine, calcium, phosphorus, and intact parathormone were measured before and after the hemodialysis session. The serum level of total bile acids [median (IQR)], in the pre-dialysis (session samples, were non-significantly higher in patients with uremic pruritus compared to those without uremic pruritus [179.89(40.8) µmol/L and 175.28 (34.2) µmol/L; respectively]; P=0.56. Serum levels of total bile acids were not correlated with the patient’s age, sex, and serum levels of urea, creatinine, calcium, phosphorous, or intact parathormone; p>0.05. Finally, serum levels of total bile acids were reduced by dialysis, and the serum levels of patients with uremic pruritus were significantly higher than those in patients without uremic pruritus in the post-dialysis session samples [133.99(23.69) µmol/L and 122.60(21.41) µmol/L; respectively]; P=0.001. In conclusion, targeting serum levels of bile acids might alleviate pruritus in chronic kidney disease patients on hemodialysis.